Quando a escrita precisa de mundo. : Quando o mundo precisa de ser escrito - Lima Ferreira, Antonieta (Revista da Associação Portuguesa de Linguística, 2019)
The teaching of writing, in the context of the Portuguese class of high school students, mobilizes reflection on how perspectives and informed opinions are built, being capable of underpinning the writing of expositoryargumentative texts. The theme to be developed in the texts is given by the present, which is configured, in its complexity, as requiring a specially informed approach. Since the world needs to be written and writing needs the world, what one teaches, learns, and evaluates must jointly consider these needs. Only in this way, it will be possible to figure what students know and how do they know how to do it, in this case, their writing competence, particularly in this textual genre. To make assessment a tool to better teach and learn.